21ST century intelligent organizations management and intellectual capital - Niño Liévano, Fabio Augusto; Rangel Pico, Angélica Nohemy; Silva Giraldo, Cesar Augusto; Gutiérrez Espalza, Alejandra María (Revista Científica Profundidad Construyendo Futuro, 2016)
he organizations of the 21st century demand from their managers capacities to face the challenges of a competition in a changing world from here that they arise constantly andin different ways about the way in which we currently provide services and how we serve a majority of the clients millennium generation; The managers of the organizations of the 21st century direct the companies in a society in constant change, how to create intellectual capital and better how to retain it in the organizations becomes one of the main decisions that the managers must take in a business world where the only constant is the change.